2018
DOI: 10.3390/coatings8120449
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Mediated Substrate Effect on the Dielectric and Ferroelectric Response of Potassium Sodium Niobate Thin Films

Abstract: If piezoelectric thin films sensors based on K0.5Na0.5NbO3 (KNN) are to achieve commercialization, it is critical to optimize the film performance using low-cost scalable processing and substrates. Here, sol–gel derived KNN thin films are deposited using a solution with 5% of potassium excess on Pt/TiO2/SiO2/Si and Pt/SrTiO3 substrates, and rapid thermal annealed at 750 °C for 5 min. Despite an identical film morphology and thickness of ~335 nm, an in-plane stress/strain state is found to be tensile for KNN fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 30 publications
(66 reference statements)
2
12
0
Order By: Relevance
“…The estimated full-width at half-maximum (fwhm) values of the rocking curves of KNN (001) shown in Figure c are 0.32°, 0.37°, and 0.40° for 20, 50, and 80 nm-thick films, respectively. However, different thermal expansion coefficient of KNN and STO is also responsible for the variation in the lattice parameter . Here, the thickness of the films are estimated from the X-ray reflectivity (XRR) patterns (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…The estimated full-width at half-maximum (fwhm) values of the rocking curves of KNN (001) shown in Figure c are 0.32°, 0.37°, and 0.40° for 20, 50, and 80 nm-thick films, respectively. However, different thermal expansion coefficient of KNN and STO is also responsible for the variation in the lattice parameter . Here, the thickness of the films are estimated from the X-ray reflectivity (XRR) patterns (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, only a minor polarization switching was observed (Figure 6). Growing the KNN films on a substrate giving tensile in-plane strain (e.g., SrRuO 3 /Pt/MgO [47], Pt/SrTiO 3 [48]) will promote in-plane polarization and should therefore promote polarization saturation when conducting in-plane measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in our recent work we have shown that substrates, used for the film deposition, also have a determining role on the final properties of the films [11]. Thus, platinized Si, mainly reported as substrate for KNN [6,7,8] and other piezoelectric films [9,10], has been shown to induce large tensile residual stress in sol–gel derived undoped KNN films due to thermal expansion mismatch, thus diminishing out-of-plane dielectric, ferroelectric, and piezoelectric response of the films [11]. On the other hand, platinized SrTiO 3 substrates, possessing much larger thermal expansion coefficient (TEC), have been shown to induce residual compressive stress in KNN films, significantly enhancing out-of-plane permittivity, polarization, and piezoresponse [11].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, platinized Si, mainly reported as substrate for KNN [6,7,8] and other piezoelectric films [9,10], has been shown to induce large tensile residual stress in sol–gel derived undoped KNN films due to thermal expansion mismatch, thus diminishing out-of-plane dielectric, ferroelectric, and piezoelectric response of the films [11]. On the other hand, platinized SrTiO 3 substrates, possessing much larger thermal expansion coefficient (TEC), have been shown to induce residual compressive stress in KNN films, significantly enhancing out-of-plane permittivity, polarization, and piezoresponse [11]. Therefore, to study only the influence of the solution conditions on the properties of polycrystalline KNN thin films, minimizing the effect of the substrate, one should choose a substrate with similar TEC.…”
Section: Introductionmentioning
confidence: 99%